2013
DOI: 10.1093/ageing/aft034
|View full text |Cite
|
Sign up to set email alerts
|

Cytophagic histiocytic panniculitis in a 74-year-old man

Abstract: Cytophagic histiocytic panniculitis is a chronic histiocytic disease of the subcutaneous adipose tissue characterised by lobular panniculitis with histiocytes containing blood cell fragments. It is also associated with marked systemic features such as fever, pancytopenia, hepatosplenomegaly, liver abnormalities and coagulopathy. We report a case of cytophagic histiocytic panniculitis in a 74-year-old man successfully treated using combination therapy with prednisolone and cyclosporine A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, preclinical and clinical studies demonstrated the applicability of [ 68 Ga]Ga‐citrate and better imaging characteristics in detection of acute osteomyelitis and intra‐abdominal infection . Based only on publications from 2013 to June 2014, the translation of 67 Ga/SPECT experience to 68 Ga/PET could potentially be useful for diagnosis of sarcoidosis, reticulohistiocitosis, osteomyelitis and discitis, diabetic foot osteomyelitis, cancer, infected aneurysm, cytophagic histiocytic panniculitis and fungal discitis . In addition, it should also be mentioned that [ 67 Ga]Ga‐citrate has been used for clinical diagnosis of lung cancer, malignant melanoma, leukaemia and some other neoplasms.…”
Section: Miscellaneousmentioning
confidence: 99%
“…However, preclinical and clinical studies demonstrated the applicability of [ 68 Ga]Ga‐citrate and better imaging characteristics in detection of acute osteomyelitis and intra‐abdominal infection . Based only on publications from 2013 to June 2014, the translation of 67 Ga/SPECT experience to 68 Ga/PET could potentially be useful for diagnosis of sarcoidosis, reticulohistiocitosis, osteomyelitis and discitis, diabetic foot osteomyelitis, cancer, infected aneurysm, cytophagic histiocytic panniculitis and fungal discitis . In addition, it should also be mentioned that [ 67 Ga]Ga‐citrate has been used for clinical diagnosis of lung cancer, malignant melanoma, leukaemia and some other neoplasms.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Various clinical manifestations have been described for CHP: subcutaneous nodules, fever, hepatomegaly, splenomegaly, lymphadenectasis, leukopenia, thrombocytopenia, anemia, elevated liver enzymes, and hemorrhagic diathesis [2]. There are less than 100 reported cases of CHP which is frequently fatal although histologically benign [3]. According to the analysis of 37 CHP patients by Ito, the mortality rate of CHP was 43.2%.…”
Section: Introductionmentioning
confidence: 99%